Pretreatment with AM1241 Enhances the Analgesic Effect of Intrathecally Administrated Mesenchymal Stem Cells - Junran Xie; Jinxuan Ren; Na Liu; Chengwei Wu; Dongju Xiao; Huanyu Luo; Jingxian Du (Stem Cells International)
Mesenchymal stem cells have cannabinoid (CB) receptors type 1 and type 2 and can alleviate a variety of neuropathic pains, including chronic constriction injury (CCI). A selective CB2 receptor agonist is AM1241. In the present study, it was found that mice with CCI displayed a longer duration of mechanical and thermal analgesia when intrathecally (i.t.) injected with AM1241-treated mesenchymal stem cells, compared to those injected with untreated mesenchymal stem cells or AM1241 alone. Moreover, CCI-induced upregulation of the phosphorylated extracellular signal-regulated kinase (ERK) 1/2 (p-ERK1/2) was inhibited following i.t. injection of AM1241-treated mesenchymal stem cells and this inhibition was noticeably higher compared to injection with untreated mesenchymal stem cells. The expression of transforming growth factor-β1 (TGF-β1) was also analyzed in the dorsal root ganglion (DRGs) and spinal cord of CCI mice. In untreated CCI mice, expression of TGF-β1 was increased, whereas pretreatment with AM1241-treated mesenchymal stem cells regulated the expression of TGF-β1 on 10 days and 19 days after surgery. In addition, i.t. injection of exogenous TGF-β1 slightly alleviated neuropathic pain whilst neutralization of TGF-β1 potently blocked the effect of AM1241-treated mesenchymal stem cells on thermal hyperalgesia and mechanical allodynia of CCI mice. In an in vitro experiment, AM1241 could enhance the release of TGF-β1 in the supernatant of BMSCs after lipopolysaccharide (LPS) simulation. Taken together, the findings of the current study show that i.t. administration of AM1241-treated mesenchymal stem cells has a positive effect on analgesia and that TGF-β1 and p-ERK1/2 may be the molecular signaling pathway involved in this process.